Analysis of Factors Influencing Poverty in South Sumatra Using the Poisson Regression Model - Manik, Jolius Saut Mangaraja; Fitri Maya Puspita; Sisca Octarina (STATMAT : JURNAL STATISTIKA DAN MATEMATIKA, 2026)
Poverty remains a key development issue for the government, including in South Sumatra Province. This study aims to analyze the factors influencing poverty levels at the district/city level using a Poisson regression model. The independent variables used include the open unemployment rate, education level, Gross Regional Domestic Product (GRDP) per capita, and the percentage of the population working in the informal sector. The data used are secondary data obtained from the Central Statistics Agency (BPS) for the most recent available year. The analysis shows that several variables significantly influence the number of poor people in South Sumatra, where increasing open unemployment and a high proportion of informal workers tend to increase the number of poor people. Conversely, increasing education and GRDP per capita contribute to reducing poverty levels. The Poisson regression model proved appropriate for modeling the number of incidents (count) data in this study. These findings are expected to provide input for local governments in formulating more targeted poverty alleviation policies.